2005
DOI: 10.4269/ajtmh.2005.73.296
|View full text |Cite
|
Sign up to set email alerts
|

Infection by Human Immunodeficiency Virus-1 Is Not a Risk Factor for Amebiasis

Abstract: The purpose of this study was to determine whether HIV-1 infected patients in our community were more susceptible to Entamoeba histolytica and Entamoeba dispar infection than non-HIV-infected individuals. The prevalence and frequency of invasive amebiasis was determined in 203 HIV+/AIDS subjects and 140 close relatives or sexual partners, all of whom were HIV-. Anti-E. histolytica antibodies (IgG, IgA) were assessed as indicators of E. histolytica invasive infection. Polymerase chain reaction (PCR) was used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 30 publications
2
31
0
1
Order By: Relevance
“…dispar mixed infections) was 25.3% compared to 18.4% in a control HIV-group. The prevalence of mixed infections in particular, as determined by PCR, was very high in HIV/AIDS patients (13.3%) compared to a control group (0.7%) (Moran et al, 2005). In the Mexican study, none of the E. histolytica-infected individuals, whether HIV-infected or not, developed clinical symptoms within 12 months.…”
Section: Prevalence Of E Histolytica Infection In Hiv/aids Patientsmentioning
confidence: 66%
“…dispar mixed infections) was 25.3% compared to 18.4% in a control HIV-group. The prevalence of mixed infections in particular, as determined by PCR, was very high in HIV/AIDS patients (13.3%) compared to a control group (0.7%) (Moran et al, 2005). In the Mexican study, none of the E. histolytica-infected individuals, whether HIV-infected or not, developed clinical symptoms within 12 months.…”
Section: Prevalence Of E Histolytica Infection In Hiv/aids Patientsmentioning
confidence: 66%
“…The consistent genetic diversity detected between the 18S rDNAs of E. histolytica and E. dispar initiated the use of 18S rDNA as a target for differentiation of the two species (31,32,36,138). DNA extracted from laboratory-cultured trophozoites and DNA recovered directly from microscopy-positive fecal samples using the manual and automated methods were tested, and the PCR methods proved to be highly sensitive and specific for detecting Entamoeba DNA (33,34,82,116,117,141,142,192,196,199). PCR assays targeting 18S rDNA are widely used for the detection and differentiation of Entamoeba species, as these targets are present on multicopy, extrachromosomal plasmids in the amebae (15), making the 18S rDNA more easily detected than a DNA fragment of a single-copy gene.…”
Section: Conventional Pcrmentioning
confidence: 99%
“…In HIV-infected patients, asymptomatic intestinal colonization shows an increase, while invasive amebiasis is less common (16). A study of 203 HIV-infected patients in Mexico City showed a prevalence of E. histolytica and/or E. dispar infection of 34.1%, but none of them developed a clinical disease during the study period (17). A study on an animal model showed that depletion of CD4+ cells diminished parasite burden and inflammation, and decreased the severity of amebic colitis (18).…”
Section: Discussionmentioning
confidence: 99%